Synergy of surface modified nanoparticles and surfactant in wettability alteration of calcite at high salinity and temperature. (1st January 2023) - Tang, Wenyue; Wu, Pingkeng; Da, Chang; Alzobaidi, Shehab; Harris, Justin; Hallaman, Brooke; Hu, Dongdong; Johnston, Keith P.
Highlights: The surface modified nanoparticles are stable under high salinity and temperature. The new nanoparticles are efficient in wettability alteration under harsh conditions. Synergy is observed between the cationic nanoparticles and cationic surfactants. The hydrophilic nanoparticles noticeably decrease the interfacial viscoelasticity. Abstract: The surface of silica nanoparticles (NPs) was modified by chemical grafting of ligands to: (1) achieve colloidal stability in concentrated brine at salinities up to 25.7 % total dissolved solids (TDS) and temperatures up to 90 °C and (2) change the wettability of carbonate reservoirs from oil-wet to water-wet. The ligand precursors included low molecular weight cationic N -trimethoxysilylpropyl-N, N, N -trimethylammonium chloride or nonionic 3-glycidyloxypropyl trimethoxysilane. The water-phase contact angle θ w of a crude oil droplet on calcite was measured for binary mixtures of the modified NPs combined with different types of surfactants, for a heavy and a light crude oil. For two types of reservoir conditions (16.7 % TDS at 55 °C and 25.7 % TDS at 90 °C), positively charged NPs with quaternary nitrogens (QNP) at 1 wt% altered the wettability of the calcite surface from strongly oil-wet (θ w  = 125° to 159°) to intermediate wet with a θ w  = 69° to 85° for light crude oil and θ w  = 71° to 107° for heavy crude oil. Meanwhile, cationic surfactants tetradecyltrimethylammonium bromide (TTAB) at 1 wt% altered the wettability to water-wet with a θ w  = 41° to 59° for light crude oil and θ w  = 70° to 90° for heavy crude oil. Synergy between the QNP and TTAB was observed in lowering the θ w by another 10°. The reduced θ w is beneficial for secondary oil recovery from carbonates, along with a significant decrease in the viscoelasticity of the crude oil-brine interface that helps destabilize undesirable water-in-crude oil emulsions.